A discussion of fault-tolerant supervisory control in terms of formal languages - Moor, Thomas (Annual reviews in control, 2016)
A system is fault tolerant if it remains functional after the occurrence of a fault. Given a plant subject to a fault, fault-tolerant control requires the controller to form a fault-tolerant closed-loop system. For the systematic design of a fault-tolerant controller, typical input data consists of the plant dynamics including the effect of the faults under consideration and a formal performance requirement with a possible allowance for degraded performance after the fault. For its obvious practical relevance, the synthesis of fault-tolerant controllers has received extensive attention in the literature, however, with a particular focus on continuous-variable systems. The present paper addresses discrete-event systems and provides an overview on fault-tolerant supervisory control. The discussion is held in terms of formal languages to uniformly present approaches to passive fault-tolerance, active fault-tolerance, post-fault recovery and fault hiding.